Reduction of transient UMP and end-winding forces by controlled switch-on of an induction motor - Van Zyl, H. J.(Hendrik Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1993.